Mengenal Huruf Hijaiyah melalui Aplikasi Marbelyah Berbasis Audio Visual bagi Siswa SD - Kika Kaniadewi Setiawan; Novi Novianti Sri Lutfiah; Rifa Aini Mulyana; Ani Nur Aeni (Departement of Mathematics Education, 2023)
Nowadays technology is getting more advanced and developing rapidly along with the times. Thus affecting various aspects of life, including in the field of education. The use of technology in the learning process is considered as one of the effective and efficient ways to help students gain a better understanding of the material being studied. One of the technologies that can be used is application. Therefore, this study aims to discuss the impact of using the Marbelyah application as a learning medium to help elementary school students in recognizing hijaiyah letters. Marbelyah is a technology-based application specifically designed to help students recognize hijaiyah letters in a more interactive and interesting way. This research uses the D&D (Design and Development) method using the ADDIE stage model. The results of the assessment were carried out by PAI teachers and students after using the Marbelyah application. From the research that has been done, the Marbelyah application gets a good value in terms of content and design. Therefore, the Marbelyah application is suitable to be used for learning media so that it can help the learning process. Thus, the application of Marbelyah as a hijaiyah learning medium can have a positive impact on PAI students and teachers in the learning process. In the future, the use of technology in education is expected to continue to be developed and improved in order to help improve the quality of learning.